Implementation of discovery learning model to improve student learning outcomes - Dyaisa Algustavia Sekar Widolaksono; Lukman Harun; Lilik Ariyanto; Agus Supriyanto (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to determine whether the discovery learning approach for teaching mathematics has an effect on students' learning outcomes. This study is quantitative descriptive research with a pre-experiment, one-group pretest-posttest research design. The research subjects consisted of 31 students from class IXA at junior high school 36 Semarang. The students took a pretest before the implementation of the discovery learning model, and then a posttest was given after the implementation to measure the enhancement of students' learning outcomes. Pretest and Posttest findings revealed an increase in the average scores, which were 47.41 and 80.90, respectively, and the N-Gain test results showed a score of 0.61 in the moderate category. The study's findings shed light on the usefulness of the discovery learning approach in increasing the learning outcomes of class IXA students at junior high school 36 Semarang, particularly in the field of geometry transformation. From the results of the pretest, it was found that 31 students were in the low category. After learning with the discovery learning model, a posttest was carried out with the results of 7 students who were in the low category, 17 students in the medium category, and 7 students in the high category. There were significant changes in the participants' pretest and posttest scores, validating the efficacy of discovery learning strategies. Students who received instruction using the discovery learning model, in particular, had considerably higher posttest results as compared to their pretest scores. This demonstrates a significant increase in their comprehension and application of geometry transformation ideas following participation in the discovery learning technique. Through the discovery learning approach, teachers play a critical role in promoting student-centered learning. While the discovery learning model has been shown to be helpful in improving student learning outcomes, it is critical to investigate other instructional strategies and the use of educational technologies in future research and teaching practices. Additional study should be conducted to explore the usefulness of instructional technology and to establish best practices for its integration in order to improve student accomplishment in the digital era.